Cardiopulmonary bypass for total aortic arch replacement surgery: A review of three techniques - Cui, Ying; Liu, Xinhao; Xiong, Jiyue; Tan, Zhaoxia; Du, Lei; Lin, Jing (Frontiers in Cardiovascular Medicine, 2023)
One of treatments for type A aortic dissection is to replace the ascending aorta and aortic arch with a graft under circulatory arrest of the lower body, but this is associated with high mortality and morbidity. Keeping the balance between oxygen supply and demand during circulatory arrest is key to reduce the morbidities and challenges the perfusion. The aim of this review was to summarize the current knowledge on the perfusion techniques and prospect the future development. Based on the perfusion area during circulatory arrest, we divided the perfusion technique into 3 types: (I) deep hypothermic circulatory arrest, (II) selective cerebral perfusion, (III) total body perfusion. Deep hypothermic circulatory arrest was first developed with cease of perfusion and provided a clear surgical field, but it is associated with high incidence of neurological complications. As selective cerebral perfusion, antegrade or retrograde cerebral perfusion can provide blood flow for the brain during circulatory arrest, resulting in less neurologic complications compared with deep hypothermic circulatory arrest. Antegrade might be better than retrograde in case of longer arrest time. In theory, total body perfusion, which can be implemented via either arterial system or venous system, or combining retrograde inferior vena caval perfusion with antegrade cerebral perfusion, provides the blood flow for all vital organs. However, whether it is better than other techniques needs further validation in large, multicenter studies. The current perfusion technique for circulatory arrest is still imperfect, and an ideal technique is evoked. Furthermore, evidence for comparing the total body perfusion with selective cerebral perfusion are also welcome to improve outcome after circulatory arrest.